Visual reaction time of drivers versus healthy adults: a comparative study - Amatya, Mrigendra; Thapa, Samjhana; Kasti, Roshan; Nepal, Ojashwi (Journal of Physiological Society of Nepal, 2020)
Introduction: Driving is a highly demanding profession requiring heightened alertness while remaining in an ergonomically constrained position and also associated with exposure to vehicular pollution and whole body vibration. We explored whether drivers’ reaction time is different to student group who also remain in sitting position for long hours but not exposed to other factors. Materials and methods: Drivers with at least one year of occupational history and under/post-graduate students were randomly selected. Their reaction time in seconds (RT) was measured by the ruler drop method (RDM) and compared with independent t test. Right vs left hand RTs were compared within groups by paired t test. Results: Thirty students (21.8±2.25 years) and 37 drivers (33.73±9.77 years) participated in the study. The drivers had RT of 2.03±0.2s on both the hands; students’ RT were 2.01±0.16s on right and 2.02±0.17s on left hands. For both hands, the differences were not significant between drivers and students (p>0.5). Right and left RT were also comparable for both groups (p>0.5). Conclusions: Bus drivers with at least one year occupational exposure have reaction times ruler drop stimulus not significantly different from controls (students).